VALUE CHAIN IN AGRICULTURE: THE CASE OF THE EUROPEAN UNION - Sanja Franc; Vlatka Bilas; Lana Trifunić (Economic Review)
The European Union (EU) provides political and strategic framework to facilitate and promote agriculture and food production. In order to adequately respond to current trends, including global coronavirus pandemic, the EU's agricultural policy should be more flexible and continue to support the active needs of European farmers. The purpose of this paper is to give an overview of the agricultural sector and Common Agricultural Policy in the EU. Focusing on the food system analysis as the key factor of sustainability and analyzing demand and supply of the food system, the main aim is to bring conclusions regarding the state and strategic role of agriculture, especially in the times of crisis when basic human needs are compromised. Scientific methods of analysis, compilation and deduction have been applied in this paper. The former two have been used for the purpose of defining agricultural value chain, its main actors and interaction among them. Through a deduction method, certain conclusions were made about the state of the EU food system as well as demand and supply trends in order to provide a broader understanding of the food security and the significance of agricultural sector in general. Although EU agriculture showed to be resilient during the pandemic, it still needs careful consideration on the adequate support measures and consistency in implementing of the existing policy and strategic measures.